Audit Trail System Support in Advanced Computer-Based Accounting Systems. - Weber, Ron (The Accounting Review, 1982)
ABSTRACT: The design of audit trails for computer-based accounting systems is not a straightforward task. The nature of the audit trail, the purposes of the audit trail, and the content of the audit trail are ambiguous. Furthermore, the operational capabilities that a system supporting the audit trail should provide is an unresolved area. Presumably, creation, deletion, and retrieval capabilities are needed, but whether modification capabilities should be provided is a contentious issue. It is an issue that becomes more important when advanced systems are implemented because errors that corrupt the integrity of the audit trail are more likely to occur. Modification capabilities may be needed for timely restoration of data integrity in the audit trail. Designing a system that supports modification capabilities for the audit trail, however, is a complex task. Using an entity-relationship model, this paper describes an audit trail system design that provides a full set of capabilities for audit trail entries: creation, deletion, retrieval, and modification. In particular, a modification strategy called "generative repair" is developed that allows a history of modifications to the audit trail to be kept intact.